Unraveling the diagnostic puzzle of eosinophilia in children - Elena Chiappini (Elsevier, 2024)
Eosinophilia is characterized by an increased eosinophil count in peripheral blood, and presents diagnostic challenges in children. Clinical manifestations can range from mild to severe, necessitating a nuanced understanding of its causes and management strategies. This narrative review provides a practice overview of eosinophilia in children, focusing on possible aetiologies and diagnostic workout. The diagnostic process is complex, requiring confirmation of eosinophilia in at least two occasions, and a step-up approach, tailored to the patient's history, symptoms and test results. In case of persistent eosinophilia, it is important that evaluations are executed timely, especially to exclude malignancy. Future research should focus on refining diagnostic algorithms for eosinophilia in children.